Researching thoughtfully - Wright, Hazel (Adult Education Discourses, 2025)
This article presents aspects of my personal journey from novice to thoughtful researcher drawing attention to things I learned along the way that may be of benefit to others travelling in the same direction. In passing, I discuss the messiness of real research, two doctoral studies (one in Geography, abandoned after data collection, and one in Education, successfully completed), my background in more scientific approaches and my more recent ventures into aspects of ethnography, auto-ethnography, auto-biography and life-writing, and with non-traditional ways of collecting, analyzing and presenting qualitative data, including fictionalization. In places, the text also draws attention to resources useful for exploring what it is to research thoughtfully.